Analysis of Economic Efficiency in Some Irish Farms Using the DEA Approach - Nicola Galluzzo (Turkish Journal of Agriculture: Food Science and Technology)
Irish farms are predominately and highly specialized in crops as cereals, protein crops and in dairy productions. The aim of this research was to estimate the economic efficiency in Irish farms part of the Farm Accountancy Data Network (FADN) dataset stratified in function of their own typology of productive specialization since 2004 to 2015 by a quantitative approach such as the Data Envelopment Analysis (DEA). Positive has been the role of inputs as financial subsidies allocated by the Common Agricultural Policy, the first and second pillar, in increasing the economic efficiency of Irish farms. Field crops farms have not had the best results in terms of the economic efficiency even if over the time, in particular during the economic crises 2008-2009, findings have not been stable with significant fluctuations and a sharply decrease of efficiency as a consequence of economic turbulences. Focusing the attention on the research outcomes in all years of investigation comparing also the different typology of farming, mixed farms and farms with animals, such as specialist cattle, sheep, goats and other grazing livestock, have had the highest levels of economic efficiency equal to 100%; by contrast Irish dairy farms have had the modest levels of economic efficiency close to 77%.